UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA HINDU TENTANG WARIGA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENTS (TGT) BAGI SISWA KELAS X MIPA-7 SMAN 1 KUTA SELATAN SEMESTER 1 TAHUN PELAJARAN 2016/2017 - I Gede Pasek Artana (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2017)
This study aims to improve the learning outcomes of Hindu and Budi Pekerti education subjects on Wariga for students of class X MIPA-7 SMA Negeri 1 Kuta Selatan through the implementation of cooperative learning model Teams Games Tournaments (TGT) held in the first semester of the academic year 2016 / 2017, which starts from September until October 2016 with the subject of research is the students of class X MIPA-7 SMA Negeri 1 Kuta Selatan 2016/2017 lesson year as many as 29 students who are Hindu. Basic Competency presented to the students is Explaining the essence of Padewasan (wariga) in the life of Hindus. This research was conducted in 2 cycles with planning, implementation, observation, and reflection on each cycle. Data collection techniques used are with the test results and observation sheet. Data analysis using comparative descriptive analysis technique by comparing the learning outcomes at initial conditions with the results achieved in each cycle, and qualitative descriptive analysis by comparing the results of observation and reflection on the cycle I and cycle II. The result of data analysis shows that there is improvement of learning quality both process and learning result. It can be seen that in the first cycle there has been an increase in the average score of 11.38 students, ie from the average score of the students at the initial conditions 66.21 to 77.59 and an increase in the average score of students 7.41 on cycle II of Average grade grade 77.59 to 85.00. While the completion of classical learning at the end of the first cycle, there was an increase of 27.59%, from the initial condition that has been completed only 51.72% to 79.31%, and there is an increase in learning mastery by 13, 79 from 79.31 % To 93.10% in cycle II. It is based on the results of observations during the learning process and the results of the assessment of knowledge about wariga after the learning process takes place. So it is suggested to the teacher especially the subject teacher of Hindu and Budi Pekerti Education to use cooperative learning model Teams Games Tournaments (TGT) in an effort to improve the learning result of Hindu Religion and Budi Pekerti.Keywords: Learning outcomes, cooperative learning, Teams Games Tournaments.